Être musulmane et sujet éthique et spirituel : Vivre-ensemble et autres concepts expérientiels mobilisés par des soufies montréalaises - Mekki-Berrada, Abdelwahed; Rousseau , Cécile; Ben Driss, Karim (Anthropologica, 2023)
Through this text, we aim to better understand the expression of subjective, ethical and aesthetic experiences of Sufi women living in Montreal, all while identifying the dynamic interactions between the key concepts they foreground. These concepts seem to form a conceptual constellation that, for these women, makes up a grid of interpretation of the world and a guide on how to act in this world. Would such a hermeneutic action, which fuses conceptualization and the experiential in the day-to-day, participate both in the construction of the self and a co-existence where difference and otherness would fall under the scope of theophany and sanctity? This is the key question we ask here. We essentially rely on qualitative data. The analysis of this data allows us to see that unpardonable atrocities, perpetrated in the world in the name of Islam by a small, violent, radical minority, organized into murderous militants and reticent to any form of otherness, should not obscure the existence of an Islam of co-existence where the Other is subject to ennoblement.